No Handmaidens Here: women, volunteering and gender dynamics in the Sydney New Theatre. Issue 2 (23rd February 2018) - Milner, Lisa; Brigden, Cathy
ABSTRACT: This paper considers the role of women in the Sydney branch of the New Theatre, from 1936 to 1969. In contrast to other gendered spaces found in the theatrical, industrial and political spheres, women held together the New Theatre. Not only did the theatre give opportunities to women as performers, but women embraced roles as directors, stage managers, writers, designers as well as holding elected offices. Drawing on oral histories and archival research, this study presents new scholarship on Australian women's leadership in the theatre, arguing that their pattern of involvement was shaped by the voluntary nature of the work, the longevity of involvement, their political commitment and the theatre's democratic structure. The blending of organisational and creative leadership created spaces for women's voices in ways that were crucial to the long-term success of the Theatre, at a time when women were generally expected to focus on the domestic sphere.